The Propagandist Role of U.S Mass Media during Wartimes: A Critical Analysis of Media Discourse in the Lead-up to the 2003 Iraq War - Chouicha,Ibtissem; Aribi, Brahim (University of Ammar Theledji -Laghouat, 2020)
Probably every conflict is fought on at least two grounds: the battlefield and the minds of the people via propaganda. The worst case scenario, however, is that propaganda has been most effective in democratic regimes in which, respect for the diversity of opinions and freedom of expression, is considered the foundation of any democratic system. Hence, this study is directed to examine the participation of U.S media institutions in crystallizing public opinion and in continuing the cycle of propaganda in the lead-up to the 2003 Iraq war. That is why the present dissertation is mainly based on the “interdisciplinary approach” of research methodology. Interdisciplinary approach involves drawing appropriately from several disciplines to redefine the propagandist role of US mass media during wartimes and to reach a deeper understanding of this complex situation. A critical discourse analysis of the mainstream media presentations is, therefore, carried out to assess their performance. CDA was chosen as the study’s method for its critical aims such as uncovering power-relations within language use or unveiling ideologies. This systematic analysis reveals that the dominant media discourse privileged the military solution option and the policies of the Bush administration. Ultimately, the failure to critically debate the administration’s positions and policies reveals the mainstream media’s failure to adequately debate issues of public importance and contributes to intensifying the crisis of democracy in which the mainstream media fail to live up to their democratic and ethical responsibilities.